Amyloid-beta peptide assembly: a critical step in fibrillogenesis and membrane disruption. - Yip, C M (2001)
Identifying the mechanisms responsible for the assembly of proteins into higher-order structures is fundamental to structural biology and understanding specific disease pathways. The amyloid-beta (Abeta) peptide is illustrative in this regard as fibrillar deposits of Abeta are characteristic of Alzheimer's disease. Because Abeta includes portions of the extracellular and transmembrane domains of the amyloid precursor protein, it is crucial to understand how this peptide interacts with cell membranes and specifically the role of membrane structure and composition on Abeta assembly and cytotoxicity. We describe the results of a combined circular dichroism spectroscopy, electron microscopy, and in situ tapping mode atomic force microscopy (TMAFM) study of the interaction of soluble monomeric Abeta with planar bilayers of total brain lipid extract. In situ extended-duration TMAFM provided evidence of membrane disruption via fibril growth of initially monomeric Abeta1-40 peptide within the total brain lipid bilayers. In contrast, the truncated Abeta1-28 peptide, which lacks the anchoring transmembrane domain found in Abeta1-40, self-associates within the lipid headgroups but does not undergo fibrillogenesis. These observations suggest that the fibrillogenic properties of Abeta peptide are in part a consequence of membrane composition, peptide sequence, and mode of assembly within the membrane.